Pengaruh Membaca dan Menonton Konten LGBT terhadap Orientasi Seksual dalam Pandangan Agama Islam - Aslamiah, Lisa; Athifah, Ghaida Nurin; Hadid, Mulyana; Fakhruddin, Agus (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2024)
Lesbian, Gay, Bisexual and Transgender (LGBT) is a form of sexual deviation that is more than adultery and sexual immorality. The presence of LGBT people in Indonesia is increasing in quantity, although the exact number is not known. The circulation of various LGBT content on social media is increasing, for example in films and various kinds of stories. This research aims to explore how much influence reading and watching LGBT content has on changes in sexual orientation. The research results show that there is an influence of reading and watching on sexual orientation. This can be seen from the results of the questionnaire, there were 3 out of 40 respondents who stated that they liked people of the same sex as a result of the influence of the reading/shows that contained LGBT elements that they read. Keywords: Islamic Education; Local Wisdom; Muslim Traditions